Nederlandse Kunst : Rijksaankopen 1989. - de Haas, Robert; Cleveringa, Piet; de Jong, Koos; Ottevanger, Alied; Noordbrabants Museum, Den Bosch (Den Haag : RBK (Rijksdienst Beeldende Kunst), 1990)
Akkerman, Philip ; Bannenberg, Peggy ; Blotkamp, Carel ; Colton, Adam ; Cremer, Jan ; Dallinga, Siert ; Eykelboom, Hans ; vanden Eynde, Patrick ; Frencken, Marliz ; Gerritsen, Ad ; Haagmans, Fons ; van Hemert, Frank ; van Hoek, Hans ; Janssen, Edwin ; Koetsier, Hans ; Kokke, Ruud Jan ; van der Laaken, Ton ; van Leeuwen, Piet ; van Lieshout, Jaap ; Lippens, Guido ; Lucassen ; Lucebert ; Peeters, Sef ; Sanders, Willem ; etc.
Nederlandse Kunst : Rijksaankopen 1989, Noordbrabants Museum, Den Bosch, 19 mei - 8 juli 1990
boek
Keywords: Nederland